Sick Leave Cuts and (Unhealthy) Returns to Work - Marie, Olivier; Vall Castelló, Judit (Journal of Labor Economics, 2023)
We investigate the impact on work absences of a large reduction in paid sick leave benefits in Spain. Our results highlight substantial decreases in frequency (number of spells) mostly offset by increases in duration (length of spells). Overall, the policy did reduce the number of days lost to sick leave. For some, however, return to work was premature, as we document large increases in both the proportion of relapses and the number of working accidents. Displacement toward this unaffected benefit scheme cancels out almost two-fifths of the gains in terms of estimated absence reductions from the sick leave benefit cut.